2015
DOI: 10.17148/ijarcce.2015.4152
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Techniques for Improving Performance of OFDM Systems for Wireless communications

Abstract: Orthogonal frequency division multiplexing (OFDM) is a special case of multicarrier transmission which transmits a stream of data over a number of lower data rate subcarriers. OFDM splits the total transmission bandwidth into a number of orthogonal and non-overlapping subcarriers and transmit the collection of bits called symbols in parallel using these subcarriers. This paper gives a total insight of various Peak -to Average Power Reduction (PAPR) techniques and principles of OFDM systems used in wireless com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Both polarizations "X" and "Y" are taken into the analysis. A comparison of proposed work and reported work [16] is shown in Table 2 in terms of log BER, input OSNR, the technique used, data rate, etc. It is observed that the proposed CO-OFDM-DSS-EC-QPSK is superior to CO-OFDM-QPSK and CO-OFDM-16QAM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both polarizations "X" and "Y" are taken into the analysis. A comparison of proposed work and reported work [16] is shown in Table 2 in terms of log BER, input OSNR, the technique used, data rate, etc. It is observed that the proposed CO-OFDM-DSS-EC-QPSK is superior to CO-OFDM-QPSK and CO-OFDM-16QAM.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results at 500 km in CO-OFDM were observed using QPSK [2] and 16 QAM comparisons. [16] In this work, a high-speed 100 Gbps CO-OFDM using a QPSK encoder is investigated with the DSS-EC technique over 500 km uncompensated link distance. Further proposed system is compared with CO-OFDM-QPSK and CO-OFDM-16QAM systems.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive radio (CR) is one technique suitable for spectrum management. This system is widely in use and has been found suitable in spectrum sensing, spectrum migration and spectrum sharing [6,7]. The operation and application of CR have been elaborately discussed in [8].…”
Section: Literature Reviewmentioning
confidence: 99%